2015
DOI: 10.1016/j.mefs.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the uterine cavity by magnetic resonance imaging, three dimensional hysterosonography and diagnostic hysteroscopy in women with pre- and post-menopausal bleeding

Abstract: Objective: To compare the diagnostic potential of magnetic resonance imaging (MRI), three dimensional (3D) hysterosonography and diagnostic hysteroscopy in evaluation of the uterine cavity in women with premenopausal and postmenopausal bleeding.Design: Comparative study. Setting: Zagazig University hospital. Materials and methods: 30 patients with premenopausal bleeding and 30 patients with postmenopausal bleeding scheduled for hysterectomy were submitted to MRI, 3D hysterosonography and hysteroscopy to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
(20 reference statements)
0
2
0
1
Order By: Relevance
“…Podczas jej stosowania znacząco rzadziej spotykano się natomiast ze zmianą stopnia złośliwości nowotworu stwierdzaną w badaniu pooperacyjnym (11) . W ostatnim czasie w bazach medycznych można znaleźć coraz więcej doniesień na temat wysokiej czułości diagnostycznej w ocenie patologii endometrium nowoczesnych badań obrazowych, takich jak transwaginalna ultrasonografia 3D czy rezonans magnetyczny (28,29) . Niewątpliwymi zaletami ww.…”
Section: Omówienieunclassified
See 1 more Smart Citation
“…Podczas jej stosowania znacząco rzadziej spotykano się natomiast ze zmianą stopnia złośliwości nowotworu stwierdzaną w badaniu pooperacyjnym (11) . W ostatnim czasie w bazach medycznych można znaleźć coraz więcej doniesień na temat wysokiej czułości diagnostycznej w ocenie patologii endometrium nowoczesnych badań obrazowych, takich jak transwaginalna ultrasonografia 3D czy rezonans magnetyczny (28,29) . Niewątpliwymi zaletami ww.…”
Section: Omówienieunclassified
“…The procedure is associated with lower rates of grading discrepancy compared to postoperative findings (11) . Recently, an increasing number of reports on the high diagnostic sensitivity in the estimation of endometrial pathology may be found in medical databases for some modern imaging techniques, such as 3D-transvaginal ultrasound or magnetic resonance imaging (28,29) . Although lower invasiveness and lower risk of complications are undoubtedly advantages of these techniques, they cannot replace the classical pathological evaluation as they do not allow for obtaining tissue samples needed for diagnosis.…”
Section: Omówieniementioning
confidence: 99%
“…MRI provides greater spatial resolution, greater contrast resolution, and superior multiplanar capabilities. Combined, this makes MRI a superior evaluator of the uterine zone anatomy (clearly differentiating subserosal, intramural and submucosal broids) and also superior in its localization of small and unusually located uterine broids and cervical broids [14,15]. Additionally, MRI can also diagnose other pelvic abnormalities and pathologies missed on the USS and is useful in assessing broid response to the treatment [7,16].…”
Section: Introductionmentioning
confidence: 99%